Basilar artery occlusion presenting as sudden bilateral deafness: a case report - Kinouchi, Tomoya (J Med Case Rep, 2021)
BACKGROUND: Most sudden-onset hearing loss is due to otolaryngologic- and very rarely to cerebrovascular disease. We report a woman with sudden bilateral sensorineural hearing loss. This case suggests that even in the absence of brainstem or cerebellar signs, magnetic resonance imaging (MRI) and MR angiography (MRA) should be performed since such studies may reveal signs of life-threatening vertebrobasilar artery occlusion. CASE PRESENTATION: A 73-year-old Japanese woman with a history of hypertension, hyperlipidemia, and atrial fibrillation who suffered bilateral deafness with vertigo and vomiting was transferred from a local hospital to our department. On admission her consciousness was clear and vertigo was absent. Neurological examination revealed only bilateral sensorineural hearing loss. Head computed tomography (CT) returned no significant findings. The next morning she gradually developed severe drowsiness. Diffusion-weighted MRI demonstrated acute cerebral infarction in the brainstem and bilateral cerebellum; MRA showed basilar artery occlusion due to a cardioembolic thrombus. Revascularization was obtained by endovascular treatment. However, her condition worsened progressively during the following hours. CT revealed new brainstem lesions, massive cerebellar swelling, and obstructive hydrocephalus. She died on the second day after her admission. CONCLUSIONS: When hearing loss is due to vertebrobasilar occlusive disease, the prognosis is very poor. We suggest that vertebrobasilar stroke be suspected in patients with bilateral sensorineural hearing loss who present with risk factors for stroke such as atrial fibrillation and other neurologic signs.